Masalah Pokok Pembangunan (Masalah Dualisme, Masalah Kependudukan Dualisme) - Fadiah Aisyah; Julfie Zahara; Gama Pratama (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study examines two key development issues in developing : economic dualism and population issues, using a qualitative approach using library research. The analysis shows that economic dualism, characterizes by the gap between the low-productivity traditional sector and the high-tech modern sector, remains a key characteristic of Indonesia’s economic structure. On the other hand, high population growth and uncontrolled urbanization exacerbate inter-regional inequality and weaken the equitable distribution of development outcomes. The interconnectedness of these two issues creates a cycle of proverty that is difficult to break and hinders the achivement of sustaineble development. Therefore, an integrative and inclusive develpment strategy is neded, encompassing strengthenung the tradisional sector, equitable imvestment, improving the quality of human resources, and controlling population growth to ensure more balanced and equitable development.